A comparative appraisal of serum progesterone level during oestrous cycle in normal and repeat breeder crossbred cows with ovulatory problem - DEKA, K C; BORGOHAIN, B N; NATH, K C; GOSWAMI, J; BISWAS, R K; DAS, P K (The Indian Journal of Animal Reproduction, 2007)
An investigation to findout variation in the levels of serum progesterone during the estrous cycle wasconducted on 117 crossbred cows; clinically the animal were catogorised as 10 normal breeders, 26repeat breeders with anovulation, 30 repeat breeders with delayed ovulation and 51 repeat breederswith normal ovulation. On day 0, IO and 18 of the oestrous cycle the respective mean serum progesteroneconcentration were recorded as 0.58 ± 0.12, 6.50 ± 0.69 and 1.08 ± 0.05 ng/ml, in normal breedercows; 0.26 ± 0.04, 0.45±0.05 and 0.25±0.04 ng/ml, in repeat breeder cows with anovulation; 0.57±0.28,4.48±0.23 and 0.99±0.05 ng/ml in repeat breeder cows with delayed ovulation and 0.59±0.04,4.76±0.14 and 1.19±0.01 ng/ml in repeat breeder cows with normal ovuiation. There was significant(P
Keywords: Serum progesterone; Repeat breeder; Crossbred cows; Anovulation; Delayed ovulation; Oestrous cycle